ANALISIS YURIDIS TERHADAP PENYELESAIAN GUGATAN SEDERHANA DI WILAYAH HUKUM PENGADILAN NEGERI PEKANBARU - Zonia, Rizkiyah Putri; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Regulation of the Supreme Court (PERMA) No. 2 Year 2015 on Procedures for Settlement of Simple Claims, PERMA is referred to as the milestone of "small claim court". A simple lawsuit is a civil suit with a $ 200,000,000.00 (two hundred million rupiah) lawsuit filed with a simple procedure and verification. The settlement of a simple lawsuit can only be used for breach of contract (wanprestasi) and / or Unlawful (PMH). The formulation of the problem, how the settlement of a simple lawsuit in the jurisdiction of the new district court under Supreme Court Regulation No. 2 of 2015 on the Procedures for Settlement of Simple Claims. What is the legal effect of a simple lawsuit on Decision Number. 01 / PDT.G.S / 16 / PN.Pbr in Pekanbaru District Court.The purpose of this research is to know the settlement of the Simple Lawsuit in Jurisdiction of Pekanbaru District Court based on Supreme Court Regulation Number 2 Year 2015 on Procedure of Settlement of Simple Claim. To know the legal effect of a simple lawsuit on Decision Number. 01 / PDT.G.S / 16 / PN.Pbr in Pekanbaru District Court. This type of research is normative that is a study that discusses the principles of law is based on applicable legislation by prioritizing library materials and its implementation in practice.Conclusion The Settlement of Simple Lawsuit in Pekanbaru District Court of Justice pursuant to PERMA Number 2 Year 2015 on Procedure of Settlement of Simple Claim in theory has fulfilled the requirement, but in practice there are some discrepancies. The time given by PERMA Number 2 Year 2015 to give notice of decision to the parties shall be 2 (two) working days after the decision is made or after the decision notification, this opens the possibility of overlapping with Article 5 Paragraph (3) which emphasizes that the settlement of the lawsuit simple 25 (twenty five) working days from the day of the first hearing. The defendant objected through the specified time due to the notice of the verdict which also passed from the specified time. This can be seen in the case implementation process with the verdict Number. 01 / Pdt.G.S / 2016 /Pn.Pbr Plaintiff Nurlelawati Boru Sinulingga with defendant Abdul Kadir.The legal consequences of a simple lawsuit on Decision Number. 01 / PDT.G.S / 2016 / PN.Pbr in the Pekanbaru District Court is final and binding after being adjudicated / comparison of the foreclosure determination by the bailiff can be executed in accordance with the applicable provisions. And punish the defendant to immediately settle all his debts of Rp.100,000,000.00 (one hundred million rupiah) to the plaintiff; and punishes the defendant to pay the case fee up to this date of Rp.2.362.000,00 (two million three hundred sixty two thousand rupiahs); reject the plaintiff's claim other than and beyond.Keywords: Simple Claim, Plaintiff and Defendant